2003
DOI: 10.1074/jbc.m208351200
|View full text |Cite
|
Sign up to set email alerts
|

The Proprotein Convertase PC5A and a Metalloprotease Are Involved in the Proteolytic Processing of the Neural Adhesion Molecule L1

Abstract: The transmembrane and multidomain neural adhesion molecule L1 plays important functional roles in the developing and adult nervous system. L1 is proteolytically processed at two distinct sites within the extracellular domain, leading to the generation of different fragments. In this report, we present evidence that the proprotein convertase PC5A is the protease that cleaves L1 in the third fibronectin type III domain, whereas the proprotein convertases furin, PC1, PC2, PACE4, and PC7 are not effective in cleav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
114
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(118 citation statements)
references
References 68 publications
4
114
0
Order By: Relevance
“…The stimulating effect of HGF on L1 shedding was also unaffected by treatment with cytochalasin D. It is possible that HGF directly stimulates metalloprotease activity, as for instance in prostate cancer cells HGF has been shown to increase cleavage of E-cadherin through activation of MMP-7 (42). For L1 it is known that membrane-proximal cleavage occurs through a metalloprotease (5,6,7) and it is suggested that ADAM10 may be one of the involved proteases (8). Although ADAM10 was recently found to be up-regulated by insulin-like growth factor 1 and epidermal growth factor in pancreatic carcinoma cells (43), no stimulation of ADAM10 by HGF has been described.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The stimulating effect of HGF on L1 shedding was also unaffected by treatment with cytochalasin D. It is possible that HGF directly stimulates metalloprotease activity, as for instance in prostate cancer cells HGF has been shown to increase cleavage of E-cadherin through activation of MMP-7 (42). For L1 it is known that membrane-proximal cleavage occurs through a metalloprotease (5,6,7) and it is suggested that ADAM10 may be one of the involved proteases (8). Although ADAM10 was recently found to be up-regulated by insulin-like growth factor 1 and epidermal growth factor in pancreatic carcinoma cells (43), no stimulation of ADAM10 by HGF has been described.…”
Section: Discussionmentioning
confidence: 99%
“…The release of L1 from the cell surface does not lead to L1 down-regulation and is therefore more likely to serve as a means for production of soluble L1. In the nervous system, soluble L1 released from cultured neurons promotes neurite outgrowth and influences neuronal differentiation (7,28). The release of soluble L1 from tumor cells may have effects on motility and spreading, as soluble L1 was shown to be deposited in the stroma of melanoma tumors and to support integrinmediated cell adhesion and migration (5,31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, L1CAM expression is seen not only in nervous tissues but has also been detected in lymphocytes, granulocytes, epithelial cells of the intestinal and urogenital tract, and in the epidermis (Thor et al, 1987;Kowitz et al, 1992;Kalus et al, 2003). L1CAM expression has also been detected in several highly malignant tumors (Deichmann et al, 2003;Fogel et al, 2003a, b).…”
Section: Discussionmentioning
confidence: 99%